1982
DOI: 10.1002/pros.2990030405
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear androgen receptor assay in biopsy‐size specimens of human prostatic tissue

Abstract: Nuclear androgen receptors in benign and malignant human prostatic tumors were estimated with a nuclear exchange assay to evaluate the applicability of the assay to biopsy size tissue samples. The mean nuclear androgen receptor content of six different prostate samples was not dependent on the amount of tissue used. In contrast, however, there was no significant correlation between the results obtained for individual prostates when large samples (500 mg) and samples weighing 100, 50(r = 0.38, n = 14), and 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We have observed that the performance of the protamine sulphate assay [18] and the nuclear androgen receptor content of BPH (Fig. 4, upper panel) are independent on the protein content of the sample.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have observed that the performance of the protamine sulphate assay [18] and the nuclear androgen receptor content of BPH (Fig. 4, upper panel) are independent on the protein content of the sample.…”
Section: Discussionmentioning
confidence: 84%
“…A method for the estimation of nuclear androgen receptors has been published [15], and recently this method has been made applicable to biopsy specimens [18]. Using relatively large samples ( -200 mg) differences have been shown in the nuclear androgen receptor content of normal and pathologic human prostatic tissue [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Their studies indicate lack of correlation between receptor site content of 50 mg and 500 mg tissue specimens from the same prostate gland. 29 In a report which appeared during the preparation of this manuscript, these investigators described significant variation in nuclear receptor site content of biopsy size tissue specimens from the same pr~state. '~ In this latter study, content was primarily measured using single determinations.…”
Section: Discussionmentioning
confidence: 99%
“…For the receptor assay used in the present study it has been shown that the mean ARn content was not dependent on the amount of tissue used (25 mg, 50 mg, 100 mg, 500 mg). We have previously reported on the validity of this single-point assay for homogenized tissue pools [5]. For actual needle biopsies a large variation in receptor values in the same tumor was found.…”
Section: Discussionmentioning
confidence: 91%